CD47/SIRPα blocking peptide identification and synergistic effect with irradiation for cancer immunotherapy - Hongfei Wang; Yixuan Sun; Xiuman Zhou; Chunxia Chen; Ling Jiao; Wanqiong Li; Shanshan Gou; Yanying Li; Jiangfeng Du; Guanyu Chen; Wenjie Zhai; Yahong Wu; et al. (Journal for ImmunoTherapy of Cancer)
Background Immunotherapy has achieved remarkable advances via a variety of strategies against tumor cells that evade immune surveillance. As important innate immune cells, macrophages play important roles in maintaining homeostasis, preventing pathogen invasion, resisting tumor cells and promoting adaptive immune response. CD47 is found to be overexpressed on tumor cells and act as a don’t eat me’ signal, which contributes to immune evasion. Macrophages mediated phagocytosis via blockade CD47/SIRPα (signal regulatory protein alpha) interaction was proved to induce effective antitumor immune response.Methods A novel peptide pep-20, specifically targeting CD47 and blocking CD47/SIRPα interaction, was identified via high-throughput phage display library bio-panning. The capability to enhance the macrophage-mediated phagocytosis activities and antitumor effects of pep-20 were investigated. The mechanism of pep-20 to induce T-cell response was explored by ex vivo analysis and confirmed via macrophage depleting strategy. The structure-activity relationship and D-amino acid substitution of pep-20 were also studied. The antitumor effects and mechanism of a proteolysis resistant D-amino acid derivate pep-20-D12 combined with irradiation (IR) were also investigated.Results Pep-20 showed remarkable enhancement of macrophage-mediated phagocytosis to both solid and hematologic tumor cells in vitro, and inhibited tumor growth in immune-competent tumor-bearing mice. Furthermore, pep-20 promoted macrophages to mobilize the antitumor T-cell response with minimal toxicity. Furthermore, systemic administration of the derivate pep-20-D12 showed robust synergistic antitumor efficacy in combination with IR.Conclusion In summary, these results demonstrated that CD47/SIRPα blocking peptides, pep-20 and its derivate, could serve as promising candidates to promote macrophages-mediated phagocytosis and immune response in cancer immunotherapy.